Purification of a DNA nicking-closing enzyme from mouse L cells. - Tang, D (1978)
A DNA nicking-closing enzyme has been purified from the nuclei of mouse L cells to 90% homogeneity. The denatured and reduced form of the enzyme has a molecular weight of 68,000 which is in agreement with the molecular weight of the native enzyme as determined by gel filtration and by sucrose sedimentation velocity assuming the protein is globular. Therefore, the active form of the enzyme is a monopolypeptide. Its isoelectric point is pH 4.2 +/- 0.2. The nicking-closing activity does not require a cofactor and does not involve any sulfhydryl group. The enzyme requires 0.2 M NaCl and pH in the range of 6.5-7.5 for optimal activity.